The Role of Peer Pressure and Parenting Style with Adolescent Delinquency in Junior High School Students: a Dimensional Analysis - Zuhrika, Zuhrika; Daharnis, Daharnis (Journal of Educational, Health and Community Psychology, 2024)
This study was motivated by the phenomenon of juvenile delinquency observed among junior high school in Padang, where students engaged in behaviors that violated social norms and school regulations, including skipping school, fighting with peers, damaging school property, participating in brawls, and bullying. A quantitative correlational approach was employed. The sample consisted 190 students from two junior high school students in Padang using purposive sampling technique. Data was collected through a Likert-scale questionnaire assessing peer pressure, parental care, and juvenile delinquency. Analysis was conducted using multiple regression with Jamovi. The findings reveal that there is a significant positive relationship between parental care and juvenile delinquency, accounting for 25.8% of the variance; and a significant relationship between peer pressure and parental care with juvenile delinquency, accounting for 25.2% of the variance. With peer pressure identified as a factor in delinquent behavior, schools could introduce regular counseling sessions that address peer dynamics, self-esteem, and resistance to negative peer influence. Peer mentoring programs could also encourage positive peer interactions and role modeling.